2018
DOI: 10.1002/jcp.26391
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNAs let‐7a, miR‐125b, miR‐100, and miR‐21 and interaction with NF‐kB pathway genes in periodontitis pathogenesis

Abstract: Periodontitis is a chronic inflammatory disease which is caused by destruction of the tissues that surrounds and supports the tooth. Deregulation of microRNAs has been reported to cause several inflammatory diseases such as autoimmune disease, chronic periodontitis, and cancer. In the present study, we have investigated the expression pattern of microRNAs let-7a, miR-125b, miR-100, miR-21, and RNA-binding protein LIN-28A among healthy individuals and chronic periodontitis patients. Total RNA was isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 25 publications
2
39
0
1
Order By: Relevance
“…MiR-21, being one of the most multi-functional miRs, is usually investigated in tumor related diseases (Selcuklu et al, 2009 ). However, increasingly intensive studies involving miR-21 have led researchers to conclude that miR-21 also plays an indispensable role in inflammation (Sheedy, 2015 ; Li et al, 2017 ; Venugopal et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-21, being one of the most multi-functional miRs, is usually investigated in tumor related diseases (Selcuklu et al, 2009 ). However, increasingly intensive studies involving miR-21 have led researchers to conclude that miR-21 also plays an indispensable role in inflammation (Sheedy, 2015 ; Li et al, 2017 ; Venugopal et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported the upregulation of let‐7a and miR‐21 as well as the reduction in miR‐125b and miR‐100 in inflamed gingiva from chronic periodontitis patients. All these four miRNAs targeted nuclear factor kappa B ( NF κ B ), which was specific to inflammation . These two studies investigated the correlation between canonical miRNA molecules and chronic periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…All these four miRNAs targeted nuclear factor kappa B (NFκB), which was specific to inflammation. 9 These two studies investigated the correlation between canonical miRNA molecules and chronic periodontitis. Nevertheless, more distinctive miRNAs featured in periodontal inflammation remained to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The intense inflammatory condition that characterizes periodontitis includes the involvement of several pathways; in particular, the correlation between NF-κB and periodontitis is widely known, as demonstrated by several clinical studies [ 38 , 39 ]. Lut 30 mg/kg decreased the levels of NF-κB and increased the expression of the cytosolic protein IκB-α, as shown from Western blot analysis performed.…”
Section: Discussionmentioning
confidence: 99%